PENGARUH KEGIATAN PAPER CLAY TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK PRA SEKOLAH USIA 4-5 TAHUN: The Effect Of Paper Clay Activities On Fine Motor Ability In Preschool Children Aged 4-5 Years - Berlian Dina Mardiana (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Early childhood is a golden age marked by rapid changes in various aspects of development. Fine motor development is an important aspect that needs to be stimulated appropriately. At Insan Cemerlang Pringsewu Kindergarten, many children experience delays in fine motor development. This research aims to determine the effect of paper clay activities on fine motor skills in pre-school children aged 4-5 years at Insan Cemerlang Pringsewu Kindergarten. This research uses quantitative methods with a quasi-experimental design with a pretest-posttest approach. The research population was pre-school children aged 4-5 years at the Insan Cemerlang Pringsewu Kindergarten, totaling 33 children. Data is collected through observation and analyzed using appropriate statistical tests. The results of the study showed that there was a significant increase in children's fine motor skills after participating in paper clay activities. Before the intervention, the average score for fine motor skills was 44, while after the intervention it increased to 55 with a p-value of .000 (<0,05). Implementation of this activity can be a useful alternative stimulation in early childhood education.